Variability in Ostariophysan Fish Brain Anatomy in Relation to the Neural Pathway of Innate Fear Response - Koenigsberg, Cynthia; Seravalli, Claudia; Schadegg, Philip (My University, 2014)
Upon exposure to odorant molecules, such as alarm substance, fish exhibit a distinct behavioral response as a result of the neural pathway that is activated by the chemical ligand. Various hypotheses have been developed for the evolutionary purpose of this phenomenon. Brain morphology variation within the Ostariophysi superorder in relation to the processing of alarm is of interest as well. The purpose of this study was to use this interdisciplinary collection of information in order to further characterize the ostariophysan alarm response.
Color poster with text, charts, and images.
Keywords: Ostariophysan alarm response; Fish brain anatomy; Posters